In Situ Proximity Ligation Assay Reveals Co-Localization of Alpha-Synuclein and SNARE Proteins in Murine Primary Neurons - Almandoz-Gil, Leire; Persson, Emma; Lindström, Veronica; Ingelsson, Martin; Erlandsson, Anna; Bergström, Joakim (Frontiers in Neurology, 2018)
The aggregation of alpha-synuclein (αSyn) is the pathological hallmark of Parkinson’s disease, dementia with Lewy bodies and related neurological disorders. However, the physiological function of the protein and how this function relates to its pathological effects remain poorly understood. One of the proposed roles of αSyn is to promote the soluble N-ethylmaleimide-sensitive factor activating protein receptor (SNARE) complex assembly by binding to VAMP-2. The objective of this study was to visualize the co-localization between αSyn and the SNARE proteins (VAMP-2, SNAP-25 and syntaxin-1) for the first time using in situ proximity ligation assay (PLA). Cortical primary neurons were cultured from either non-transgenic or transgenic mice expressing human αSyn with the A30P mutation under the Thy-1 promoter. With an antibody recognizing both mouse and human αSyn, a PLA signal indicating close proximity between αSyn and the three SNARE proteins was observed both in the soma and throughout the processes. No differences in the extent of PLA signals were seen between non-transgenic and transgenic neurons. With an antibody specific against human αSyn, the PLA signal was mostly located to the soma and was only present in a few cells. Taken together, in situ PLA is a method that can be used to investigate the co-localization of αSyn and the SNARE proteins in primary neuronal cultures.